2021
DOI: 10.3390/ijerph182212241
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Local Community Leaders, Health Care Workers, Volunteers, Policy Makers and Academia on Climate Change Related Health Risks in Mukuru Informal Settlement in Nairobi, Kenya—A Qualitative Study

Abstract: Sub-Saharan Africa has been identified as one of the most vulnerable regions to climate change. The objective of this study was to explore knowledge and perspectives on climate change and health-related issues, with a particular focus on non-communicable diseases, in the informal settlement (urban slum) of Mukuru in Nairobi, Kenya. Three focus group discussions and five in-depth interviews were conducted with total of 28 participants representing local community leaders, health care workers, volunteers, policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Given the scale of recent agricultural damages due to extreme climate events in India, their widespread coverage and importance in the region, this was high on the list of perceived climate impacts. This included downstream effects of agricultural impacts on health through food systems, as was also seen in other multi-stakeholder studies from other settings, pointing to the interlinked nature of climate impacts [ 14 , 36 , 37 ]. As was also discussed by participants as an indirect impact of climate change, reduced agricultural yield due to climate change has been linked to a loss of work hours, which in turn can potentially lead to sedentary lifestyles, causing further risk of ill health and malnutrition [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Given the scale of recent agricultural damages due to extreme climate events in India, their widespread coverage and importance in the region, this was high on the list of perceived climate impacts. This included downstream effects of agricultural impacts on health through food systems, as was also seen in other multi-stakeholder studies from other settings, pointing to the interlinked nature of climate impacts [ 14 , 36 , 37 ]. As was also discussed by participants as an indirect impact of climate change, reduced agricultural yield due to climate change has been linked to a loss of work hours, which in turn can potentially lead to sedentary lifestyles, causing further risk of ill health and malnutrition [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 73%
“…This could potentially explain why participants deemed common and easily observed climate risks and health impacts, such as agriculture and vector-borne diseases, greater than others, such as CVD impacts. Vector-borne diseases are commonly considered to be highly climate-sensitive, partially due to their explicit nature and monsoon climate, which fosters stagnant water [ 36 , 37 ]. There have also been reports of increased flooding along the eastern coast of India in recent years [ 33 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of awareness was attributed to factors such as a lack of local policy, regulatory authority, trained public health staff, funding, scientific information, and political support (Rahman et al, 2021). In Mukuru, Nairobi, Kenya, a qualitative study conducted in 2021 found that local community leaders, health workers, volunteers, policymakers, and academics in the area recognized a range of climate-related health impacts, including lung disease, heat stroke, and hypertension (Andersen et al, 2021). In particular, they highlighted the significant negative impacts of climate change on mental health, underscoring the need for comprehensive policies that address both physical and mental well-being.…”
Section: Understanding Of and Engagement With Climate Change And Heal...mentioning
confidence: 99%
“…Mukuru is the second largest informal settlement with eight villages located on an estimated 647 acres of land in Embakasi South Constituency in Nairobi County 18 . It was purposively selected because of its rapid growth and potential for the upsurge of respiratory health risks among residents 19 and the dominance of PAYG customers. (Fig 1).…”
Section: Study Locationmentioning
confidence: 99%